Teaching Games for Understanding in Game Performance and Psychosocial Variables: Systematic Review and Meta-Analysis of Randomized Control Trial - Marcos Ortiz; Lourdes Meroño; María T. Morales-Belando; Raquel Vaquero-Cristóbal; Noelia González-Gálvez (MDPI AG, 2023)
Different authors have reported on the influence of the Teaching Games for Understanding (TGfU) intervention on game performance and psychosocial variables. This review aimed: (a) to explore the TGfU experimental studies; (b) to compare the effects of the TGfU vs. technical approach pedagogy on game performance; and (c) to determine the effect of the TGfU approach on game performance and psychosocial variables (motivational climate, task orientation, perceived competence and enjoyment). This systematic review with meta-analysis adheres to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Four databases (PubMed, WOS, EBSCO and Google scholar metasearch) were searched. Study quality was measured with the Physiotherapy Evidence Database (PEDro) score. Thirteen studies were included. A pooled analysis of all interventions demonstrated a large significant improvement in decision making for TGfU when compared to technical approach pedagogy (SMD = 5.93, I2 = 98%; CI (95%) = 2.15-9.71; p = 0.004) and no differences between groups for skill execution (SMD = 1.70; I2 = 8%; CI (95%) = −5.34-8.73; p = 0.60). The effect of a TGfU intervention on game performance is strong (decision making, execution skills and tactical skills). Moderate evidence is reported by psychosocial variables (motivational climate, task orientation, perception of motivation and achievement in physical education). In addition, it is unclear its effect on perceived competence, enjoyment, knowledge of the game and intention to be physically active. TGfU intervention could be an appropriate approach for males and females in the context of education or sport. There is a need for a greater number of studies.